The Period of Perineal Wound Healing in Postpartum Mothers Between The Decoction Water Treatments of Bihanong Leaves with Red Betel Leaves - Nahdiyah Karimah; Nur Khafidhoh; Triana Sri Hardjanti; Riska Ismawati Hakim (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The global prevalence of the second degree of the perineal wound of postpartum mothers is 73.4%. Pharmacological treatments have a cytotoxic effect. Other treatments is non-pharmacological treatments are such as using decoc on waters of binahong leaves and red betel leaves. Both have compounds that accelerate epithelializa on of wounds. This study aims to analyze the differences of the perineal wound recovery period of postpartum mothers between the decoc on water treatments of binahong leaves compared to red betel leaves. Methods: This study is a quasi-experiment post-test only without control group design. There are 32 respon- dents mee ng the inclusion criteria who are taken by accidental sampling. The sample is divided equally into two groups, namely binahong group and the red betel group. Binahong or red betel leaf decoc on waters are used for genital washing a er urina ng at the last rinse at 7 am and 3 pm on 1-3 postpartum days. Perineal wound recovery is assessed by using the REEDA score from the second postpartum day un l the wound fully recovered. Sta s c analysis with chi-square, me series analysis, Mann Whitney and Kruskal Wallis test. Results: The average of perineal wound recovery period of binahong group is 6 days, while the red betel group is 4.69 days. There are significant differences of perineal wound recovery period between the binahong group and the red betel group with a p-value of 0.0001 < α (0.05). Respondents’ characteris cs are age, BMI, frequency of changing pads, and educa onal background between binahong and red betel groups have no significant differ- ences. Conclusion: Red betel leaf decoc on water is recommended for postpartum mothers suffering perineal wounds. Further research is needed with a larger number of respondents and true experiments are needed to analyze the effect of red betel leaves on perineal pain, platelets, and leukocyte level.